2016
DOI: 10.1515/macvetrev-2015-0063
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Pasteurella Multocida from Farm Pigs in Serbia

Abstract: The investigations covered a total of 234 lungs from necropsied pigs with different pneumonic lesions, from 6 farrow-to-finish pig farms during 2013 and 2014. The samples were inoculated on selective culture media and aerobically incubated at 37 o C and in carbon dioxide condition. The isolated bacterial colonies were further characterised morphologically and biochemically. The identification was confirmed using the BBL Crystal, E/N, G/P ID Kit (Becton Dickinson). For determination of the type of Pasteurella m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…A significant reduction of resistance for these two antimicrobial agents might have occurred as a result of their reduced usage during recent years, especially in treating animals from the category 15-40 kg of body weight. In several previous Serbian studies (27,33,35) it was found that the most common respiratory bacterial pathogens in pigs were Pasteurella multocida, A. pleuropneumoniae and Haemphilus parasuis. Generally, in the treatment of infections caused by these pathogens tetracycline and trimethoprim/sulfamethoxazole are less efficient in comparison to other antibiotics, so this may partly explain the reduced usage of these two drugs in veterinary practice in Serbia.…”
Section: Methodsmentioning
confidence: 93%
“…A significant reduction of resistance for these two antimicrobial agents might have occurred as a result of their reduced usage during recent years, especially in treating animals from the category 15-40 kg of body weight. In several previous Serbian studies (27,33,35) it was found that the most common respiratory bacterial pathogens in pigs were Pasteurella multocida, A. pleuropneumoniae and Haemphilus parasuis. Generally, in the treatment of infections caused by these pathogens tetracycline and trimethoprim/sulfamethoxazole are less efficient in comparison to other antibiotics, so this may partly explain the reduced usage of these two drugs in veterinary practice in Serbia.…”
Section: Methodsmentioning
confidence: 93%